Maritime industry development institute a proposal - Valenzona, Salvador
The importance of the maritime industry to the national economy cannot be understated. The industry has to be properly developed in order for the country to reap the fruits of comparative advantage possessed in other economic fields. Any inadequacy of existing service will serve as a barrier to the attainment of the country's growth objectives. For purposes of this paper, the maritime industry refers to the business of designing, construction, manufacturing, acquiring, operating, supplying, repairing and/ or maintaining vessels or component parts thereof; of managing and/or operating shipping lines, stevedoring arrastre and customs brokerage services, shipyards, drydocks, marine railways, amrine repair shops, shipping and freight forwarding agencies and similar enterprise. Specifically, the full development and growth of the industry will yield benefits to the nation in terms of: 1. Increased production and productivity in the various islands and regions of the archipelago through the provision of an effective linkage; 2. enhanced competitive position of the Philippine vessels in the carriage of the country' foreign trade; 3. strengthen balance of payments position through the reduction in dollar expenditures for ship importation and freight payment; 4. the generation of greater revenues and earnings by the maritime and other related industries; 5. the full impact of the multiplier effect in generating growth not only in the maritime industry but also in related and supportive industries and attendant employment generation; 6. further technological development of allied industries in response to the maritime industry's needs; 7. the attainment in the long-run of the much sought cultural integration, national unit, increased productivity and self-reliance; 8. improve the competitive position of the country's products in world markets; 8. improved passenger safety and comfort not only for tourists but also for domestic travellers. recognizing the vital role the industry plays in national development efforts, the university of the Philippines College Cebu hereby proposes the establishment, organization and institutionalization of the Maritime Industry Development Institute (MIDI). The objectives of the Institute are: 1. To promote the development of the essential knowledge and skills in the area of maritime management and operations; 2. To initiate the systematic and comprehensive compilation of information vital to the management and operation of the maritime industry; 3. To extend technical assistance to individuals, institutions and organizations involved in the industry towards improved management of the industry and other related industries. The institute shall require an amount of ₱57.074 million or ₱60 million to round it off, over the next five years starting on academic school year 1977. Twenty-five million pesos will be spent on acquisition of land and construction of a building for the institute, ₱30 million on equipment and the balance for operations. Funding support shall be requested from individuals, associations and institutions who in one way or another will benefit from the establishment of the Institute. Also included in the sources of funding will be those institutions whose main concern is the assistance of efforts for development. The total amount needed by the Institute shall be divided between domestic and foreign sources on a 50-50 basis.